A Study on the Causes of Academic Procrastination in Thesis Completion among English Undergraduate Students - Carita Septia Nanda; Eliwarti; M. Syarfi (Universitas Islam Negeri Palopo, 2026)
Academic procrastination is a widespread phenomenon among university students, particularly among English undergraduates when completing their final academic requirement, the thesis. Utilizing a qualitative research design with a phenomenological approach, this study aims to explore how students experience academic procrastination during the process of thesis completion and to identify the causes behind this behavior. Ten final-year undergraduate students (five from the 2020 cohort and five from the 2021 cohort) of the English Study Program at FKIP Universitas Riau were selected using a purposive sampling. The data were collected through semi-structured interviews and analyzed using thematic analysis. The findings revealed that (1) tendencies of academic procrastination in thesis completion were evident, as reflected in procrastination in starting the thesis, procrastination in working on thesis, gaps between planned and actual action, and preferring more enjoyable activities; and (2) the causes of academic procrastination can be categorized into internal and external factors. Internal factors included psychological conditions (low motivation, unstable mood, laziness, stress, anxiety, fear of making mistakes, and confusion), physical conditions (fatigue due to academic and work demands and illnesses), and linguistic and conceptual challenges. External factors involved environmental conditions, family-related issues, supervision-related issues, institutional issues, and social (peer) issues.